Potential of citronella oil as natural mosquito repellent agent in formulated fabric softener finishes / Aznin Baharudin... [et al.] - Baharudin, Aznin; Jani, Nor Akmalazura; Azreen, Azyati; Assyura, A. A.; Pornomo, Hawa; Mehat, M. Hafiz (Univeristi Teknologi MARA, Sabah, 2020)
This study is focused on formulating a natural-based fabric softener using baking soda and vinegar with the addition of insect repellent finish of citronella oil and vanillin. The effectiveness of the fabric softener was evaluated by conducting a fabric stiffness test on both untreated and treated fabric samples with the softener formulated in this study. The assessment for the efficacy of insect repellence was carried out using 3 human participants of the same gender and build but different blood type, positioned at a mosquito infested area. Three tests; negative, positive, and normal tests were conducted to evaluate the effectiveness of the formulated mosquito repellent finishes in the fabric softener. The results show that the formulated fabric softener is good mosquito repellent and it is good at giving a soft effect on the treated fabric.